Edukasi Permainan Tradisional Siswa Sekolah Dasar di SDN 2 Telaga Jaya - Ruslan, Ruslan; Datau, Suriyadi; Tumaloto, Ella H; Mile, Sarjan; Daipatimu, Moh Rifki; Laboro, Darmansyah; Tahir, Nanda (Universitas Negeri Gorontalo, 2026)
The development of digital technology has caused a shift in lifestyle in elementary school-aged children, namely physical activity has begun to be replaced by the use of gadgets. This condition has an impact on the decline in students' literacy skills related to knowledge and gross motor skills. The purpose of this community service activity is to reintroduce and educate traditional games at SDN 2 Telaga Jaya. The method used in this service is participatory education which includes observation, socialization and evaluation. The focus of the games educated includes Kalari, Tenggedi Buawu (Stilts), Jump Rope, and Sack Run. The results of the activity showed a significant increase in aspects of knowledge, skills, and attitudes. Based on the post-test results, students were able to practice game techniques with a better level of balance and dexterity, in addition, this traditional game stimulates social interaction and sportsmanship of students during recess. Traditional game education has proven effective as a fun medium for learning character and physical health. It is recommended for schools to integrate these games into the school's routine agenda to ensure the sustainability of the preservation of local wisdom.